Realization of Tunable Highly-Efficient Quantum Routing in Chiral Waveguides - Yan, Guo-An; Lu, Hua (Frontiers in Physics, 2022)
The chiral interaction between single photons in waveguides and quantum emitters has gained considerable attention. Here, we proposed a tunable quantum routing scheme with a chiral quantum system by coupling an emitter to two chiral waveguides. Conventional quantum routers can only be achieved with each port output probability no larger than 25%. But our scheme can transfer quantum information arbitrarily from an input port to another, and each port’s output probability is 100%. Besides, we investigated the influence of the Purcell factor in quantum routing properties. No matter how to change the size of the directionalities Sj or set a specific value to the dissipation of the emitter, we always found that the quantum routing has very high efficiency. Moreover, we also used a superconducting qubit coupled to two resonators to show the present scheme is pretty feasible for experimental implementation.